A Review of Insulin Degludec/Insulin Aspart: Pharmacokinetic and Pharmacodynamic Properties and Their Implications in Clinical Use - Haahr, Hanne (Clin Pharmacokinet, 2016)
Insulin degludec/insulin aspart (IDegAsp; 70 % IDeg and 30 % IAsp) is a soluble combination of two individual insulin analogues in one product, designed to provide mealtime glycaemic control due to the IAsp component and basal glucose-lowering effect from the IDeg component. The pharmacokinetic and pharmacodynamic characteristics of IDegAsp have been investigated in a series of clinical pharmacology studies with generally comparable designs, methodologies and patient inclusion/exclusion criteria. The glucose-lowering effect profile of IDegAsp during once-daily dosing at steady state shows distinct and clearly separated action from the prandial and basal components of IDegAsp. The IAsp component provides rapid onset and peak glucose-lowering effect followed by a flat glucose-lowering effect lasting beyond 30 h due to IDeg. During twice-daily dosing, the distinct peak effect and the flat basal effect are retained following each dose. The pharmacological properties of IDegAsp are maintained in the elderly, children, adolescents, Japanese patients and those with hepatic or renal impairment. The potential clinical benefits associated with the pharmacological properties of IDegAsp have been verified in phase III clinical trials comparing IDegAsp with three other currently available treatment options: premixed insulin, basal-bolus regimens and basal-only therapy. IDegAsp shows favourable clinical benefits compared with biphasic insulin aspart 30 and is a viable alternative to basal-bolus and basal-only therapy. This review presents the results from clinical pharmacology studies conducted with IDegAsp to date, and extrapolates these results to clinical use of IDegAsp in the context of findings from the IDegAsp clinical therapeutic studies.